Pengaruh Aspek Pemasaran, Aspek Teknik, Dan Aspek Keuangan Studi Kelayakan Bisnis Terhadap Pendapatan Peternak Walet Di Kecamatan Lalan Kabupaten Musi Banyuasin Sumatera Selatan - Irsan Irsan; Kemas Welly Angga Permana (LPPM Universitas Multi Data Palembang, 2021)
The purpose of this research was to find out how the feasibility study of the swallow farm business in Lalan sub-district, Musi Banyuasin, South Sumatra in terms of financial, marketing and technical aspects. So that it can be seen the amount of funds needed for an investment in swallow farm business. Then it was analyzed to determine the effect of these three aspects (financial, marketing, and technical aspects) on the income of swallow breeders either partially or simultaneously. In addition, it was also to determine which feasibility aspect has the most dominant influence on farmer income. The research method was a quantitative descriptive approach, there are 279 samples of 926 swallow breeder businesses. The data analysis used in this study was multiple linear regression statistical analysis (t test and F test). The results of the analysis show that the financial, marketing, and technical aspects simultaneously have a significant effect on swallow breeders’ income, while partially, only the marketing and technical aspects have a significant effect. Of the three variables, the marketing aspect has the most dominant influence on the income of swallow breeders